Strategi Humas Dalam Menjaga Citra Positif Pemerintah Kota Malang Di Era Keterbukaan Informasi Publik - Sihidi, Iradhad Taqwa; Caroline, Anugrah Dinda (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2022)
Public Information Disclosure is an important aspect of democracy that can create a good governance system. The Law on Public Information Disclosure that has been stipulated by the Government aims to enable all public agencies or bodies to provide easy access to any information needed by the public. Public relations is an important thing in implementing a system that can affect the image of the Malang City Government. From this research, that is to know the strategy of Public Relations in maintaining a positive image of the Malang City Government in the era of public information. The theory used in this study is the Government Public Relations Strategy according to Rosady Ruslan which includes that the Government has a link in understanding to meet the needs of the community. This study uses a qualitative descriptive method which data collection is done by means of interviews, observation and documentation. The results of this study are the strategies that have been carried out by Public Relations in maintaining a positive image of the Malang City Government in the current era of public information found by optimizing information media through Instagram and the Website, expanding collaboration from various media, collecting and analyzing daily news by sorting positive tone news. which is used as a form of evaluation, the involvement of the Mayor and Deputy Mayor of Malang in community activities to maintain closeness public with the Malang City Government.